HUBUNGAN KARAKTERISTIK PEGAWAI DAN KEPUASAN KOMPENSASI DENGAN KINERJA PEGAWAI DI RUMAH SAKIT X DI DENPASAR - Anggareksa, I Putu Ryanatista; Suarjana, I Ketut; Ekawati, Ni Komang (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p22, 2025)
ABSTRACT X Hospital is an organization that routinely provides compensation. Compensation is a factor that affects employee performance. However, compensation is still a problem in 2018 - 2022 and also an issue of employee performance. This study aims to determine the relationship between employee characteristics and compensation satisfaction with employee performance at X Hospital in Denpasar. This research is a quantitative study with an observational research design with a cross sectional approach. The sample of this research is employees who are registered as employees of 79 employees. The sampling technique uses probability proportional to size (PPS). This study used a questionnaire with descriptive and bivariate statistical analysis methods. The results showed that the majority of employees were aged ? 30 years (73.4%), female (69.6%), university education (97.5%), permanent employment status (68.4%), years of service > 5 years (75.9%), service group (62%), satisfied with compensation (67.1%), and good performance (81%). There is a relationship between length of service (p-value = 0.023) and compensation satisfaction (p-value = 0.016) with employee performance. There still dissatisfaction with compensation and poor performance. It is hoped that in providing compensation, the hospital will be guided by performance evaluation and employees will further improve their attitude of responsibility. Keywords : Employee Characteristics, Compensation Satisfaction, Employee Performance